Conceptual Bases of Target Agreements’ Signing in the Context of Strategic Management of Higher Educational Institutions of Federal Republic of Germany - Gladchenko, Myroslava (Pedagogical Discourse, 2013)
Conceptual bases of target agreements’ signing in the sphere of management of higher education institutions in Federal Republic of Germany, which were formulated in the resolution of the Conference of rectors of higher education institutions of Federal Republic of Germany have been analyzed. Practical experience of the use of the target agreements as an instrument of implementation of strategic planning in the sphere of higher education highlighted by the German scientists has been studied.